Introducing photonics - Culshaw, Brian (Cambridge: Cambridge University Press, 2020)
"The essential guide for anyone wanting a quick introduction to the fundamental ideas underlying photonics. The author uses his 40 years of experience in photonics research and teaching to provide intuitive explanations of key concepts, and demonstrates how these relate to the operation of photonic devices and systems. Gain insight into the nature of light and the ways in which it interacts with materials and structures, and learn how these basic ideas are applied in areas such as optical systems, 3D imaging and astronomy. Carefully designed worked examples and end-of-chapter problems enable students to check their understanding, with full solutions available online. Mathematical treatments are kept as simple as possible, allowing readers to grasp even the most complex of concepts. Clear, concise and accessible, this is the perfect guide for undergraduate students taking a first course in photonics, and anyone in academia or industry wanting to review the fundamentals"--
Includes bibliographical references and index.
Keywords: Photonics